The environmental benefits of reusing wastewater in landscape watering - Noor Nabilah , Mazlan (2012)
Nowadays, the wastewater has been used in variety application. Sewage effluent is a major source of water pollution in our country whereas in other countries. With proper water quality control, sewage effluent can also be considered as a potential resource for specific applications. Therefore, this study was carried out to establish the potential of reusing sewage effluent from wastewater treatment plants to irrigate landscape plants. This study aims to gather more information about the suitability of the effluent in landscape irrigation. Besides, we also aims to determine the reduction of effluent discharge and cost if this wastewater reuse is practiced. Furthermore, it is found that sunlight could reduce the concentration of F. coli and E. coil at surface of landscape plants. The quality of treated effluent from selected oxidation pond of University Malaysia Pahang was found to be suitable for irrigation.